3D Microporous Lanthanide–Organic Frameworks Constructed from Left‐ and Right‐Handed Helical Chains: Synthesis, Crystal Structure, and Tunable Photoluminescence. Issue 5 (19th January 2015) - Huo, Rui; Li, Xia; Ma, Dou
Abstract: New lanthanide–organic frameworks, [Ln2 (2, 6‐NDS)3 (IP)(H2 O)4 ]· H2 O Ln = Sm (1 ), Eu (2 ), Tb (3 ); 2, 6‐NDS = 2, 6‐Anaphthalenedisulfonate, IP = 1 H ‐imidazo[4, 5‐ f ][1, 10]‐phenanthroline, were synthesized and characterized. These complexes are isostructural and have three‐dimensional structures (3D) composed of a pair of entanglement double helixes. The structure is an open framework with rhombic channels filled with uncoordinated water molecules. The photoluminescence properties of the Sm III complex (1 ) and Eu III /Tb III ‐doped complex were explored by adjusting the excitation wavelengths. Interestingly, Sm III complex1 generated a white‐light emission, whereas the Eu III /Tb III ‐doped complex (Tb0.95 Eu0.05 ) allowed the realization of white‐light emission under broad UV wavelengths. An energy transfer for Tb III 5 D4 →Eu III 5 D0 was observed. Abstract : Lanthanide frameworks were assembled from 2, 6‐naphthalenedisulfonate and 1 H ‐imidazo[4, 5‐ f ][1, 10]‐phenanthroline. They have 3D microporous structures constructed from left‐ and right‐handed helical chains. The Sm III complex and the Eu III /Tb III ‐doped complex allowed the realization of luminescence tuning and white‐light emission.